Transcription of killer virion double-stranded RNA in vitro. - Welsh, D (1980)
Intracellular virions of stationary phase ethanol-grown cells of a killer strain of Saccharomyces cerevisiae contain encapsulated M (1.1 x 10(6) dalton) and L (3.2 x 10(6) dalton) double-stranded RNA plasmids. These virions also contain RNA polymerase activity which catalyzes the synthesis of full-length, single-stranded, asymmetric transcripts (denoted m and l) of the virion double-stranded RNAs. Product m is made by M-containing particles and shows complete sequence homology to M but not to L. Product l is made by L-containing particles and shows complete homology only to L. The products show no self-homology, indicating asymmetric transcription. Therefore, the polymerase appears to function in vitro as a double-stranded RNA transcriptase. The lack of sequence homology between M and L is confirmed.